Knockdown of hsa_circ_0023028 inhibits cell proliferation, migration, and invasion in laryngeal cancer by sponging miR-194-5p. Issue 6 (14th June 2019) - Chen, Xiaofeng; Su, Xiaoqing; Zhu, Chuansai; Zhou, Jing
Abstract : Emerging evidences have proposed that circular RNAs (circRNAs) play a major role in carcinogenesis. Hsa_circ_0023028 has been reported to be aberrantly expressed in laryngeal cancer (LCa). However, the role and the mechanism of hsa_circ_0023028 in LCa have not been adequately studied. In the present study, we demonstrated that hsa_circ_0023028 expression was up-regulated in LCa tissues and cell lines. miR-194-5p was down-regulated in LCa cells. Functionally, knockdown of hsa_circ_0023028 inhibited the proliferation, migration, and invasion of LCa cells, as evidenced by the reduced number of 5-Ethynyl-2′-deoxyuridine (EdU)-positive cells and decreased number of migrated and invaded cells. Additionally, hsa_circ_0023028 was identified as an miR-194-5p sink. A negative correlation between miR-194-5p and hsa_circ_0023028 expression was observed in LCa tissues. Besides, down-regulation of miR-194-5p attenuated the inhibitory effects of hsa_circ_0023028 silencing on LCa cell proliferation, migration, and invasion. In summary, hsa_circ_0023028 functions as an miR-194-5p sponge to promote the proliferation, migration, and invasion of LCa cells.